Physique and performance for track and field events - O'Connor, H.; Olds, T.; Maughan, R. J. (Journal of Sports Sciences, 2007)
Evidence of the importance of physique in the athletics disciplines is supported by the persistence of certain characteristics over long periods, despite marked secular changes in the source population. These characteristics may also result in physiological benefits such as effective thermoregulation or a greater power-to-weight ratio. Coaches and athletes are often convinced of weight or fat loss benefits based on personal or anecdotal experience, intuition, and "trained eye" observation of successful competitors. This may entice athletes into adopting unbalanced, erratic or highly restrictive eating patterns that increase the risk for nutrient deficiencies, and disordered eating. Despite heavy training loads and often extreme diets, some athletes fall short of their physique goals as ultimately phenotype is under genetic control. Professionals assisting athletes with physique management need to be highly skilled in anthropometry and require a thorough understanding of sports-specific nutrition requirements. Careful assessment of the risks and benefits of various approaches to weight and fat loss is required before they are recommended to athletes.